PERTUMBUHAN DAN PRODUKSI KACANG TANAH (Arachis hypogaea L.) PADA BERBAGAI DOSIS KALIUM ORGANIK - Syamsia Syamsia; Sampara Sampara; Abuakar Idhan; Rosanna Rosanna; Irwan Mado (Agroplantae: Jurnal Ilmiah Terapan Budidaya dan Pengelolaan Tanaman Pertanian dan Perkebunan, 2023)
Organic potassium fertilizer and liquid organic fertilizer are an alternative to reduce the use of chemical fertilizers in peanut cultivation. This research aims to determine the dose of organic potassium, the dose of liquid organic fertilizer (LOF) from cow urine on the growth and production of peanuts. This research was structured using a Randomized Block Design (RBD) with 2 treatments, namely doses of organic potassium and cow urine liquid organic fertilizer (LOF). The parameters observed were plant height (cm), number of leaf stalks (stalk), seed weight per 1000 (g), number of pods (fruit), fresh weight (g), and dry weight (g). The results of the study showed that treatment with doses of organic potassium and cow urine LOF had no significant effect on the growth and production of peanuts. The best organic potassium dose for growth and production is organic potassium equivalent to a KCl dose of 75 kg ha-1. The best dose of cow urine LOF is 75 ml L-1.